Implementation of acute care patient portals: recommendations on utility and use from six early adopters. (4th September 2017) - Grossman, Lisa V; Choi, Sung W; Collins, Sarah; Dykes, Patricia C; O'Leary, Kevin J; Rizer, Milisa; Strong, Philip; Yen, Po-Yin; Vawdrey, David K
Abstract: Objective: To provide recommendations on how to most effectively implement advanced features of acute care patient portals, including: (1) patient-provider communication, (2) care plan information, (3) clinical data viewing, (4) patient education, (5) patient safety, (6) caregiver access, and (7) hospital amenities. Recommendations: We summarize the experiences of 6 organizations that have implemented acute care portals, representing a variety of settings and technologies. We discuss the considerations for and challenges of incorporating various features into an acute care patient portal, and extract the lessons learned from each institution's experience. We recommend that stakeholders in acute care patient portals should: (1) consider the benefits and challenges of generic and structured electronic care team messaging; (2) examine strategies to provide rich care plan information, such as daily schedule, problem list, care goals, discharge criteria, and post-hospitalization care plan; (3) offer increasingly comprehensive access to clinical data and medical record information; (4) develop alternative strategies for patient education that go beyond infobuttons; (5) focus on improving patient safety through explicit safety-oriented features; (6) consider strategies to engage patient caregivers through portals while remaining cognizant of potential Health Insurance Portability and Accountability Act (HIPAA) violations; (7) consider offering amenities to patients through acute care portals, such as information about navigating the hospital or electronic food ordering.